Pre-calving Intravaginal Administration of Lactic Acid Bacteria Reduces Metritis Prevalence and Regulates Blood Neutrophil Gene Expression After Calving in Dairy Cattle - Genís, Sandra; Cerri, Ronaldo L. A.; Bach, Àlex; Silper, Bruna F.; Baylão, Matheus; Denis-Robichaud, José; Arís, Anna (Frontiers in Veterinary Science, 2018)
Metritis affects up to 40% of dairy cows and it is usually treated with antibiotics. In spite of their advantages, there is an increased concern about antibiotic resistance leading to the research of alternative methods. The aim of this study was to evaluate the effects of a combination of lactic acid bacteria (LAB) on the prevalence of metritis and modulation of endometrial and neutrophil inflammatory markers in dairy cows. One hundred and thirty-five cows were enrolled 3 wk before calving and randomly assigned to three treatments. Treatment groups were: (1) two intravaginal doses of LAB/wk during 3 wk pre-calving (vaginal, n = 45); (2) an intra-uterine dose, once 1 d after calving (uterine, n = 44); and (3) no intervention (CTRL, n = 45). Metritis was defined as body temperature > 39.5° C and purulent vaginal discharge (> 50% pus), and diagnosed 6 d after calving. Blood samples were taken at d -14, -10, -7, -4, +1, +3, +6, +14 relative to calving for non-esterified fatty acids (NEFA) analysis. At d -10, +1, +3, and +6 neutrophils were isolated from blood for gene expression analysis by RT-qPCR. Endometrium biopsies were taken from 30 cows, 15 from CTRL and 15 from the uterine group at d +1, +3, and +6 after calving for pro-inflammatory markers analysis by NanoString®. Vaginal treatment reduced metritis prevalence (6/45) up to 58% compared with CTRL group (14/45), but there was no difference between the uterine and CTRL group. Uterine and vaginal treatments reduced blood neutrophil gene expression. Expression of pro-inflammatory markers in the endometrium did not differ between uterine and CTRL cows. Metritic cows expressed more C-X-C motif chemokine ligand 8 (CXCL8) and interleukin 1 beta (IL1B) at d 3 than healthy cows, whereas healthy cows expressed more CXCL8 at d 1 relative to calving in the endometrium. This study shows a promising potential of LAB probiotics as a preventive treatment against metritis in dairy cows.